The impact of breast cancer on social cognition in female Colombian patients - Nicole Palacio; Daniela Nicole Romero; Andrés Mateo Bernal; Daniela González-Rodríguez; Daniel Solarte-Bothe; María del Pilar García; Raúl Murillo; Hernando Santamaría-García; Sandra Báez (BMC Psychology, 2022)
Abstract Background The high prevalence of female breast cancer is a global health concern. Breast cancer and its treatments have been associated with impairments in general cognition, as well as structural and functional brain changes. Considering the social challenges that some of these patients face, it is important to understand the socio-emotional effects of breast cancer as well. Nevertheless, the impact of breast cancer on social cognition has remained underexplored. The objective of this study was to assess social cognition domains and other relevant cognitive and emotional variables (executive functions, anxiety, or depression) in females with breast cancer. Methods The participants were 29 female patients diagnosed with breast cancer and 29 female healthy controls. We assessed emotion recognition, theory of mind, empathy, and moral emotions. We also included measures of general cognitive functioning, quality of life, anxiety, and depression. Linear multiple regressions were performed to assess whether the group (patients or controls), GAD-7 scores, emotional and social subscales of EORTC QLQ-C30, and IFS scores predicted the social cognition variables (EET, RMET, MSAT). Results Patients with breast cancer showed impairments in emotion recognition and in affective theory of mind. In addition, patients had lower scores in some executive functions. Only theory of mind between group differences remained significant after Bonferroni correction. Emotion recognition was associated with executive functioning, but anxiety levels were not a significant predictor of the changes in social cognition. Conclusions Social cognition impairments, especially in theory of mind, may be present in breast cancer, which can be relevant to understanding the social challenges that these patients encounter. This could indicate the need for therapeutic interventions to preserve social cognition skills in patients with breast cancer.